A new aerodynamic decoupled frequential FDIR methodology for satellite actuator faults. (16th January 2013) - Baldi, P.; Castaldi, P.; Mimmo, N.; Simani, S.
SUMMARY This paper presents new results regarding the development of a supervision scheme for a nonlinear satellite model. The main issue concerns the handling of frequency faults affecting the reaction wheels of a spacecraft attitude control system, that is, how to detect and isolate faults, how to determine the different frequencies characterising these faults through spectral analysis and lastly, how to prevent propagation into failures with potential mission abortion as a consequence. Thus, this work investigates the design of a scheme for fault detection, isolation and control reconfiguration applied to the reaction wheels of a spacecraft attitude control, based on the satellite model. This scheme is classifiable as active fault tolerant control. As the study focuses on a general satellite nonlinear model, where aerodynamic and gravitational disturbances, as well as measurement errors, are present, the robustness of the suggested strategy is achieved by exploiting an explicit disturbance decoupling method via a nonlinear geometric approach. To achieve accurate fault diagnosis, aerodynamic disturbance decoupling represents the key point because the aerodynamic model is often uncertain. Moreover, an improvement of the nonlinear geometric approach is presented, to realise both aerodynamic and manoeuvre decoupled fault diagnosis. To the best authors' knowledge, this is the first works presenting a methodology for frequency fault diagnosis, which is based on the nonlinear geometric approach for fault and disturbance decoupling. The obtained results demonstrate that the proposed methodology can achieve better performances with respect to traditional fault detection and isolation schemes. Copyright © 2013 John Wiley & Sons, Ltd.